Penerapan Self Help Menggunakan Ayat-ayat al-Qur’an (Studi Naratif Menghadapi Jatuh Cinta dan Patah Hati) - Putri Laras Trisnawati; Maya Tsuroya Alfadla (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Mental health is currently a growing issue in Indonesia. Mental health is a balanced state and the achievement of individual development tasks. Individuals who are facing poor mental health will develop self-narratives that tend to be destructive. Self-narrative is an individual's life story consisting of values, experiences and identities that are internalized into a belief and personality. Self-destructive narratives affect individual development. Problems that are closely related to depression experienced by individuals are falling in love and heartbreak. These problems provide stress effects to depression to individuals. Depression contributes the greatest value to suicide rates. The method used is qualitative research with narrative approach. The subject strengthens his inner values through the study of the verses of the Qur'an and self-evaluation in a series of self-help processes. Self help consists of the process of understanding the values of life in the verses of the Qur'an, evaluating relationships with the Almighty and preparing for the worst. The subject has a perspective and meaning related to falling in love and broken heart experienced and internalized into self-narration. Self-narration is developed based on the results of self-help that is done so that it can bring up new meanings in life.